Optimisation of PHEV/EV charging infrastructures: A review - Rahman, I. (Inderscience Publishers, 2014)
Plug-in hybrid electric vehicle (PHEV) or electric vehicle (EV) has the potential to facilitate the energy and environmental aspects of personal transportation, but face a hurdle of access to charging system. The charging infrastructure has its own complexities when it is compared with petrol stations because of the involvement of the different charging alternatives. As a result, the topic related to optimisation of PHEV/EV charging infrastructure has attracted the attention of researchers from different communities in the past few years. Recently introduced smart grid technology has brought new challenges and opportunities for the development of electric vehicle infrastructure facilities. This paper is a review of different computational approaches and techniques used for the optimisation of charging infrastructure for electric vehicles. Copyright Â© 2014 Inderscience Enterprises Ltd.